Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.bbrc.2017.04.060
|View full text |Cite
|
Sign up to set email alerts
|

WDR5 positively regulates p53 stability by inhibiting p53 ubiquitination

Abstract: WD40 repeat protein WDR5 is a core component of the Set/MLL histone methyltransferase complex which catalyzes histone H3 Lys4 trimethylation and activates gene transcription in human cells. WDR5 promotes Set/MLL complex assembly and mediates the complex binding to Lys4-dimethylated histone H3 tail. Most earlier studies report that WDR5 exerts profound effects on various cellular and organismal processes mainly through epigenetic regulation of gene transcription. However, the functions of WDR5 in lung cancer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Interacts with p53 during ESC Specification Next, we sought to explore the mechanism(s) by which WDR5 regulates p53. We found that Wdr5 extended void did not alter p53 transcripts (Figure 7A) (Sun et al, 2015;Xie et al, 2017). We noticed that ChIP-seq peaks representing WDR5 bound to RP genes were overrepresented (Figures S4E and S7A; data not shown).…”
Section: Wdr5 Regulates P53 Protein Stability and Directlymentioning
confidence: 83%
“…Interacts with p53 during ESC Specification Next, we sought to explore the mechanism(s) by which WDR5 regulates p53. We found that Wdr5 extended void did not alter p53 transcripts (Figure 7A) (Sun et al, 2015;Xie et al, 2017). We noticed that ChIP-seq peaks representing WDR5 bound to RP genes were overrepresented (Figures S4E and S7A; data not shown).…”
Section: Wdr5 Regulates P53 Protein Stability and Directlymentioning
confidence: 83%
“…The scores of positively stained cell percentage were delineated as: score 1 for <25% positive cells; score 2 for 25%-50% positive cells; score 3 for 50%-75% positive cells; score 4 for 75%-100% positive cells. The final score ranged from 0 to 12, and the cut-off was identified by receiver operating characteristic (ROC) curve as previous studies ( 22 , 26 ). Our cohort was separated to WDR5 low and WDR5 high subsets based on the cut-off of IHC score, which was defined as 3.0 in our study.…”
Section: Methodsmentioning
confidence: 99%
“…In lung cancer, WDR5 is reported to promote proliferation of lung adenocarcinoma by inducing SOX9 expression ( 21 ). In LC cell line A549 cells, WDR5 positively regulates P53 stability and arrests A549 cell cycle in G1 phase ( 22 ), which is conflicting with most studies indicating WDR5 as a tumor-promotor. However, the expression and clinical indications of WDR5 in BM from NSCLC are still unknown.…”
Section: Introductionmentioning
confidence: 94%
“…WDR5 can form protein complexes with transcription factors to regulate gene transcription. Recent studies have revealed that WDR5 plays key roles in the tumorigenesis and progression of a variety of cancers, such as breast cancer [27], neuroblastoma [28], pancreatic cancer [29], prostate cancer [30], gastric cancer [31] and non-small cell lung cancer [32,33]. However, similarly, its roles in colon cancer are less understood.…”
Section: Introductionmentioning
confidence: 99%